1996
DOI: 10.1046/j.1525-1438.1996.06020120.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease-free interval and recurrence pattern after the Okabayashi variant of Wertheim's radical hysterectomy for stage IB and IIA cervical carcinoma

Abstract: From January 1982 to December 1991 271 patients underwent radical hysterectomy according to the Okabayashi modification for cervical carcinoma stage IB and IIA. Intraoperative complications occurred in 3.3%. The urinary fistula rate was only 2.2%. The 5‐year Disease‐free Interval (DFI) was 90%. In a univariate analysis tumor size 3 cm (n = 99), positive pelvic nodes (n = 53), adenocarcinoma (n = 58) and parametrial involvement (n = 36) were all associated with a significantly decreased DFI. Recurrence occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 14 publications
1
25
0
5
Order By: Relevance
“…Tumor stage has also been defined as a prognostic factor in many studies; better outcomes were reported with early stages [19][20][21]. In our series, the 5-year overall survival varied according to the clinical stages, it was 81 and 66 % in stages I and II and 32 and 12 % in stages III and IV, respectively.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Tumor stage has also been defined as a prognostic factor in many studies; better outcomes were reported with early stages [19][20][21]. In our series, the 5-year overall survival varied according to the clinical stages, it was 81 and 66 % in stages I and II and 32 and 12 % in stages III and IV, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…Samlal et al [20] and Nakanishi et al [16,19] both found that 5-year disease-free interval (94 and 90 %, respectively) and survival were significantly affected by the lymph node status. In their studies, when squamous carcinoma was compared to adenocarcinoma, no difference was found between the two histological types when lymph node metastases were absent.…”
Section: Discussionmentioning
confidence: 98%
“…Plusieurs études ont impliqué la radicalité de l'exérèse du LUS dans la survenue de complications postopératoires urinaire et rectale dans le cadre de l'hystérectomie extrafasciale étendue pour cancer [5][6][7][8][9][10][11]. Les étapes chirurgicales à haut risque de lésion nerveuse sont la résection du LUS, des ligaments vésico-utérins (piliers de la vessie) et du paracervix (ligament cardinal, de Mackenrodt) [2][3][4].…”
Section: Discussionunclassified
“…Il en est ainsi lors d'une colpohystérectomie totale élargie distale avec curage interiliaque, le traitement de référence pour les cancers du col utérin débutants stade FIGO IA2 à IIA, responsable d'une morbidité fonctionnelle importante à long terme [5][6][7][8][9]. Il s'agit le plus souvent de patientes jeunes âgées entre 30 et 50 ans.…”
Section: Introductionunclassified
See 1 more Smart Citation